Application value of blood metagenomic next-generation sequencing in patients with connective tissue diseases - Su, Rui; Yan, Huanhuan; Li, Na; Ding, Tingting; Li, Baochen; Xie, Yuhuan; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2022)
Objective: This study aimed to anlyze the application value of blood metagenomic next-generation sequencing (mNGS) for in patients with Connective tissue diseases (CTD) to provide a reference for the infection diagnosis and guidance for treatment. Methods: A toal of 126 CTD patients with suspected infections who were hospitalized in the department of Rheumatology, the Second Hospital of Shanxi Medical University from January 2020 to December 2021 were enrolled in this study. We retrospectively reviewed the results of mNGS and conventional diagnostic tests(CDT). Results: Systemic lupus erythematosus (SLE) and polymyositis/dermatomyositis (DM/PM) had the highest incidence of infections.The positive pathogens detection rates of mNGS was higher than that of CDT. The virus infections are the most common type in CTD patients with single or mixed infection, especially Human gammaherpesvirus 4(EBV), Human betaherpesvirus 5(CMV) and Human alphaherpesvirus 1. The incidence of prokaryotes and eukaryotes infections are secondary to viruses. Bloodstream infections of rare pathogens such as Pneumocystis jirovecii should be of concern. Meanwhile, the most common mixed infection were bacterial–virus coinfection. Conclusion: mNGS has incremental application value in patients with CTD suspected of co-infection. It has a high sensitivity, and a wide detection range for microorganisms in CTD patients. Furthermore, the high incidence of opportunistic virus infections in CTD patients should be of sufficient concern.